(untitled) (Vallis Aurea, 2022)
This research aims to analyze and understand the influence of typology of defender and prospector strategies on company performance by using moderation of environmental uncertainty. This research is an explanatory study using a quantitative approach with survey methods. This research uses a questionnaire instrument that researchers distribute to managers of companies listed on the Indonesia Stock Exchange (IDX). Data analysis uses moderation regression analysis (MRA). The results showed that the typology of defender and prospector strategies significantly affected the company’s pe